Effects of Aqueous Ethanolic Extract of the leaves of Guiera senegalensis J.F. Gmel (Combretaceae) on Liver Function in Wister Strain Albino Rats - and M.A. Geidam, M.A. Oshobu (International Journal of Scientific Research and Management (IJSRM), 2017)
The effects of different doses of aqueous ethanolic extract of the leaves of Guiera senegalensis on liver function test of wister strain albino rats were investigated at high doses of 1000mg/kg and 2000mg/kg which showed high toxicity with some clinical signs but at lower doses of 100mg/kg, 150mg/kg and 200mg/kg, showed little or no effects on the liver function tests (AST, ALT, TP, ALK-PH, and ALB). Of these only ALK-PH showed significant increase (P